Evaluation of mTOR signaling pathway proteins in rat gastric mucosa exposed to sulfite and ghrelin - Ercan, Sevim; Şahin, Pınar; Kencebay, Ceren; Derin, Narin; Çelik Özenci, Çiler (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Mammalian target of rapamycin (mTOR) signaling serves as a central regulator of cell growth, proliferation, and survival. In this study, we planned to evaluate the expressions of mTOR signaling constituents (p-p70S6K, p-mTOR, and p-Tuberin) in rat gastric mucosa and to compare the results in sulfite- and sulfite+ghrelin-exposed groups. Materials and Methods: Rats were divided into three groups: the control group (C), the sodium metabisulfite (Na2S2O5) (S) group, and sulfite+ghrelin (SG) group. Sodium metabisulfite at 100 mg/kg/day was administered via gavage, and ghrelin at 20 µg/kg/day was administered intraperitoneally for 35 days. We have used immunohistochemistry for mTOR signaling pathway components. Results: There were no significant differences for p-p70S6K and p-mTOR expression among the C, S, and SG groups. Tuberin expression was significantly increased in the S group compared to the C group. Furthermore, tuberin expression was found to be significantly decreased in the SG group. Conclusion: This study is the first one in the literature that shows the expression of mTOR signaling proteins in gastric mucosa of rats exposed to sulfite and ghrelin. Furthermore, it demonstrates that ghrelin treatment reduces p-Tuberin expression induced by ingested sulfite. Cite this article as: Ercan S, Şahin P, Kencebay C, Derin N, Çelik Özenci Ç. Evaluation of mTOR signaling pathway proteins in rat gastric mucosa exposed to sulfite and ghrelin. Turk J Gastroenterol 2018; 29: 90-6.